Early Cretaceous Volcanic Edifice Activity in the Sulu Orogenic Belt: Evidences From Volcanic-Sedimentary Rhythm Characteristics in Lingshan Island, Eastern Shandong Province, China - Liu, Ruiyang; Zhou, Yaoqi; Dong, Shihui; Zhou, Tengfei; Mu, Hongyu; Bai, Bingyang; Li, Sunyi; Chen, Tongtong; Zhang, Zhenkai (Frontiers in Earth Science, 2022)
A rhyolitic tuff-mudstone interbedded rock outcrop with a good rhythm is found in the Yangjiaodong area of Lingshan Island, eastern Shandong Province. The volcanic eruption dynamics process was investigated by using the rhythm of volcanic accumulation method. Combined with the geologic setting of the study area, the parameter deposition rate is 6.5 m/Ma, and the mudstone compaction factor is 0.3 because the study area is the Ri-Qing-Wei Basin, which is the volcanic back-arc basin with insufficient source supply. Based on this, the time span of the analyzed sample was calculated to be 2.24 Ma, which represents the duration of this eruption event. We used software called Acycle to finish this research. The result shows cyclicity of 2.296, 5.78, 8.475, and 15.625 kyr and the scales of 2.17, 2.94, 3.12, and 18.87 m repeatability. Considering that magma eruption is affected by changing melt conditions, the crystallinity, water content, temperature, and pressure are comprehensively considered “activation conditions” to predict the dynamic process within the near-surface magma chamber, which is characterized using a pulsed volcanic eruption model.